2019
DOI: 10.1007/s42452-019-0932-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the performance of GFRP/wood-based honeycomb sandwich panels for sustainable prefab building construction

Abstract: The static failure behavior of innovative wood-based sandwich panels with wood-based core and face sheets made of glass fiber reinforced polymer was investigated. The sandwich panels were subjected to three-point bending and compression tests to determine their strengths and their failure mechanisms. The honeycomb core of medium density fiberboard (MDF) was manufactured to reduce the weight of the whole panel as well as the consumption of wood elements. The hollow portions of the honeycomb core were filled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A novel solution of composite shear keys is presented in order to minimize the influence of imperfections created in the production process and trying to raise the safety and stability of sandwich structures. The shear keys can be inserted into the core of sandwich laminate to prevent the delamination of the skins due to the shear loads, as explained in [37], [38] and [39].…”
Section: Sandwich Delaminationmentioning
confidence: 99%
“…A novel solution of composite shear keys is presented in order to minimize the influence of imperfections created in the production process and trying to raise the safety and stability of sandwich structures. The shear keys can be inserted into the core of sandwich laminate to prevent the delamination of the skins due to the shear loads, as explained in [37], [38] and [39].…”
Section: Sandwich Delaminationmentioning
confidence: 99%
“…Weight reduction and better shear and compression properties should be considered for the core layer. Therefore, materials with lower density, such as foam plastic [9], honeycomb structure [10], wood material [11] and so on, can be selected as the core layers. Because sandwich structural composites have the advantages of high bending stiffness and light-weight, they have been widely used in medical equipment, aerospace, sports, wind power and other fields [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in order to improve the mechanical properties and the efficiency of the MDF, researchers have shown that using glass fiber reinforced laminates as a face sheet can be used to produce MDF-cored sandwich panels [11]. Hussain et al [12] have studied the application of hollow MDFs as a core layer in the production of sandwich panels with face sheets made of glass fiber reinforced polymer and showed that the MDF honeycomb structures were superior due to their capacity to sustain against the load after failure, although the mechanical characteristics of the solid MDF were similar when compared to the MDF honeycomb panels. Hassan et al [13] have evaluated the separation strength between the glass fiber/epoxy laminates as face sheets with the MDF core layer and showed that the strength at the interfaced layer was stronger than the debonding of the core layer based on UF resin.…”
Section: Introductionmentioning
confidence: 99%